Supply chain Management practices of retail RMG fashion industry of Bangladesh: A study on Sailor By Epyllion - Khan, Md. Rakib Hasan (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2021.